Values, accountability and trust among Muslim staff in Islamic organisations - Nasution, Hasnah; Ahmed Shihab, Saman; Al-Hawary, Sulieman Ibraheem Shelash; Pallathadka, Harikumar; Al-Salami, Ammar Abdel Amir; Van, Le; Al-Khafaji, Forqan Ali Hussein; Morozova, Tatiana Victorovna; Muda, Iskandar (Hervormde teologiese studies, 2023)
While humans are the best of creations and God’s caliphs on Earth, such a status is always hard to achieve and necessitates many efforts and too much practice. This world also has a two-way path, one terminating in the lowest of the low and the other culminating in the highest of the high. It means that one way leads to misfortune and misery and the other to happiness and perfection. To attain happiness, accountability can be of utmost importance. Besides, the purpose of human creation is closeness to God by preferring the right path, which is not often possible unless they speak the truth and make the best use of the enlightening teachings of the revelation to spot the bad and good, becoming aware of their own duties and responsibilities and ultimately putting them into effect. This research aimed to investigate the mediating role of values in the relationship between accountability and trust among Muslim managers and employees in Islamic organisations, using a descriptive method through a field study. The statistical population included 2500 senior Muslim managers and employees of Iraqi government organisations, selected via simple random sampling. In this research, structural equation modelling (SEM) analysis was recruited for data analysis in the Statistical Package for the Social Sciences (SPSS) and Analysis of a Moment Structures (AMOS). The study results demonstrated that accountability in Muslim managers and employees has a significant positive effect on trust (p = 0.45) and values (p = 0.81). Moreover, the findings revealed that values have a positive effect on reinforcing trust in Islamic organisations (p = 0.54), and above all bolster the relationship between accountability in managers and employees and organisational trust (p = 0.43).ContributionThe accountability of managers and employees can have a positive effect on individuals’ performance in organisations. In general, psychological pressures in organisations result in organisational transformation and then maintain values through trust-building. Such changes can be subsequently operationalized and have a profound impact on people’s behaviour by affecting work order and keeping them always growing, agile and diligent, in order to reach a new level of performance.